Dermacoccus sp. isolated from a brain abscess in a 4-year-old child. Issue 12 (December 2019) - Ivaska, Lauri; Alyazidi, Raidan; Hoang, Linda; Goldfarb, David M.
Abstract: Dermacoccus spp. have rarely been reported as human pathogens. We describe a case of a 4-year-old boy with congenital heart disease who was diagnosed with a brain abscess. The abscess was drained and the sample grew Streptococcus intermedius, Aggregatibacter aphrophilus and Dermacoccus sp.. Dermacoccus grew after 5 days of incubation and the patient was treated with meropenem.